Pengaruh Pengawasan Keuangan Daerah dan Kompetensi SDM terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Simeulue - Uni Mawarnisa (Universitas Cenderawasih, 2025)
Financial statements are a form of government management's accountability in presenting information related to financial positions to stakeholders. This study aims to determine the influence of regional financial supervision and human resource competence on the quality of local government financial statements in Simeulue Regency. This study involved 45 District Government Work Units (SKPK) with a total of 90 financial managers as respondents, who were selected using the purposive sampling method. The hypothesis test was carried out using multiple linear regression analysis with SPSS software version 23. The results of the analysis show that, partially, regional financial supervision and human resource competence significantly affect the quality of local government financial statements in Simeulue Regency. Simultaneously, the two variables were also found to have a significant effect on improving the quality of the financial statements of the local government of Simeulue district.